Penerapan Terapi Realitas Teknik WDEP untuk Meningkatkan Penerimaan Diri WBS Panti Bina Insan Bangun Daya - Rahmawan, Farah Rizki; Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The East Jakarta Bina Insan Bangun Daya II Social Institution itself accommodates various characteristics of people with social welfare problems (PMKS) that disturb public order. Some of the WBS in the orphanage are socioeconomically vulnerable women. Most of the WBS already have children, have been abandoned or divorced from their husbands, and have uncertain jobs, so they end up on the street. Brought to an orphanage for training. However, during WBS coaching, they showed negative behaviours such as being emotionally unstable, irresponsible, difficult to accept circumstances, blaming themselves, and being alone. Calhoun and Acocella (1995) explain that selfacceptance is related to a positive self-concept, and with a positive self-concept, a person can accept and understand facts that are so different from himself. Self-acceptance is the ability to accept everything that is in oneself, both the strengths and weaknesses that are possessed. To increase self-acceptance in WBS assisted by Reality Therapy with the WDEP Technique, which was carried out in 10 sessions. The results of measuring self-acceptance used a selfacceptance scale based on Sheerer’s theory (1957) in the form of a pre-test and post-test, resulting in findings of a change in self-acceptance in the WBS of 43% from the medium to high category.